Pendidikan Karakter Siswa SD Dalam Pandangan Islam - Wibawati Bermi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2020)
Character education is a very important issue to be implemented in all levels of education including in elementary schools. Character education in elementary school is an attempt to build character Elementary Students. Character education can be called as akhlak (moral) education, which aims to establish akhlak karimah. The foundation of character education in Islam is the Quran and Hadith. The process of character education to elementary school students should be tailored to the stage of development and the formation of character at this age, in elementary operations can use the model Tadzkirah (Teladan=Exemplary, Arahkan=Aim,Dorongan=Encouragement,Zakiyah=purify,Kontinuitas=Continuity,Ingatkan=Remind, repitition, Organize, Heart). Keywords: character education, akhlak (moral), tadzkirah.